2020
DOI: 10.5267/j.uscm.2019.7.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply chain practices on performance through supply chain integration in textile and garment industry of Vietnam

Abstract: This paper is intended to evaluate intermediary role of SCI in the relationship between supply chain management practices (SCMP) and supply chain performance (SCP) and, at the same time, to examine the regulatory role of firm size and transformational leadership in this relationship. The research is conducted on 536 Vietnamese textile and garment enterprises and the results show that SCI had a complete intermediary role in the relationship between SCMP and SCP. Additionally, Size and Transformational leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…In general, business environment mentioned resources, factors or organizations affecting to business activities and performance (Le et al, 2019;Phan et al, 2019). Business environment is divided into two types including internal business environment and external business environment.…”
Section: Mediating Role Of Supply Chain Management Performancementioning
confidence: 99%
“…In general, business environment mentioned resources, factors or organizations affecting to business activities and performance (Le et al, 2019;Phan et al, 2019). Business environment is divided into two types including internal business environment and external business environment.…”
Section: Mediating Role Of Supply Chain Management Performancementioning
confidence: 99%
“…High or low business performance depends on the level of organization of production and management of each enterprise (Phan et al, 2019). Business performance is an economic category in depth, reflecting level of exploitation of resources and level of cost for such resources in the reproduction process to achieve business goals (Phan et al, 2019). The production and business performance today become important for economic growth and they are basis for assessing implementation of economic goals of the enterprise in each stage.…”
Section: Business Performancementioning
confidence: 99%
“…Five main contents of financial performance include: (1) short-term solvency, (2) business activities, (3) financial leverage, (4) profitability capacity, and (5) enterprise value considered through groups of common evaluation index (Saeidi et al, 2015;Phan et al, 2019;Nguyen et al, 2016).…”
Section: Business Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that there was a significant relationship between supply chain management practices and supply chain performance. In addition, Phan et al (2020) examined the effect of supply chain management practices represented in information sharing, information quality, supplier relationship and customer relationship on supply chain integration. Findings proved a significant relationship between Supply Chain Management Practices and supply chain integration.…”
mentioning
confidence: 99%